2020
DOI: 10.2217/cns-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Automated histologic diagnosis of CNS tumors with machine learning

Abstract: The discovery of a new mass involving the brain or spine typically prompts referral to a neurosurgeon to consider biopsy or surgical resection. Intraoperative decision-making depends significantly on the histologic diagnosis, which is often established when a small specimen is sent for immediate interpretation by a neuropathologist. Access to neuropathologists may be limited in resource-poor settings, which has prompted several groups to develop machine learning algorithms for automated interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…AI algorithms are effective in detecting these minute differences for accurate diagnosis. 26,56 In a study by Krivoshapkin et al (2016), MRI histogram peaks were used to formulate the AI algorithm to study the tumor volumes. By Tukey test and the Games-Howell test, the authors identified the mean deviation in agreement index between specialists (neurosurgeons and radiologists) was 0.98 ± 0.007 (±SEM).…”
Section: Preoperative Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…AI algorithms are effective in detecting these minute differences for accurate diagnosis. 26,56 In a study by Krivoshapkin et al (2016), MRI histogram peaks were used to formulate the AI algorithm to study the tumor volumes. By Tukey test and the Games-Howell test, the authors identified the mean deviation in agreement index between specialists (neurosurgeons and radiologists) was 0.98 ± 0.007 (±SEM).…”
Section: Preoperative Diagnosismentioning
confidence: 99%
“…Various authors mention that by deploying computer algorithms, the accuracy of diagnosis and inter-operator repeatability can be improved. 26,56 While many factors make the neurosurgical procedure successful, the surgeon's planning and competency are integral. AI algorithms have proven helpful in these aspects by improving anatomical delineation and enriching simulation-based training.…”
Section: Summary Of the Contentmentioning
confidence: 99%
“…This may aid surgeons in making more accurate surgical decisions to avoid unnecessary lung function loss and related complications. Future studies should consider using deep learning to quantitatively analyze paraffin sections (used to determine neurological tumor pathology) (37) and intraoperative FS images to incorporate them into the model, improving the model accuracy and increasing the objectivity of intraoperative FS analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…7,33,34 The large data sets generated from SRH can lend themselves to ML approaches to rapidly classify tissue. Orringer et al, have developed ML approaches to enable automated diagnosis of CNS tumours from their SRH imagesas reviewed by Khalsa et al 35 Their approach has evolved from using vector-based multilayer perceptron (MLP) which are trained using specialised knowledge of CNS tumours to manually define important features (nuclear morphology, cell density, vascularity, etc.) and can result in biasing of data, 10 to using deep CNN that retain spatial information and learn what image features are important in determining diagnosis and predicting patient outcomes.…”
Section: Computer Aided Diagnosismentioning
confidence: 99%